2015
DOI: 10.5897/ajb2014.13908
|View full text |Cite
|
Sign up to set email alerts
|

First detection of bla TEM, SHV and CTX-M among Gram negative bacilli exhibiting extended spectrum -lactamase phenotype isolated at University Hospital Center, Yalgado Ouedraogo, Ouagadougou, Burkina Faso

Abstract: Resistance to a wide variety of common antimicrobials is observed among clinical strains designed as extended spectrum β-lactmase (ESBL) producers. They produce enzymatic protein which inactivates efficiently oxyimino cephalosporin and constitutes a serious global health concern that has complicated treatment strategies. Many studies report high prevalence of ESBL producers among Gram negative bacilli. The aim of this work was to identify the presence of TEM, SHV and CTX-M families in these strains which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
(25 reference statements)
3
1
0
Order By: Relevance
“…The bacteria that showed higher levels of resistance were Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae. The same observation was previously made in Burkina Faso (27,28).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The bacteria that showed higher levels of resistance were Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae. The same observation was previously made in Burkina Faso (27,28).…”
Section: Discussionsupporting
confidence: 81%
“…Kamga et al (33) observed a strong presence of TRI (inhibitor-resistant TEM) in Escherichia coli strains, which may justify the high presence of TEM in the Escherichia coli strains isolated in the present study. Zongo et al (28) in Burkina Faso, Salah (34), and Diagbouga et al (35) in Togo also found that the bla-Tem gene was the most widespread in ESBL-producing Escherichia coli strains, whereas Bla-SHV was the predominant gene in ESBL-producing Klebsiella pneumonia strains. However, the high proportion of bla-CTX-M in Togo (95.7%) and Burkina Faso (65.49%) is not the same as in our study because this gene came second after bla-Tem and represented only 18%.…”
Section: Discussionmentioning
confidence: 94%
“…(17.65%), and E. coli (14.71%), followed by S. aureus (13.72%).The screening of ESBL producers in our finding was done by Double Disc Synergy Test. The total ESBLs producers in the result of the recent study were Similar to that reported in other studies : (29) ; (30); (31) ,the disagreement with our finding reported by (32). The highest ESBLs Producer in all Groups was E.coli .…”
Section: Discussionsupporting
confidence: 76%
“…According to Zongo et al [51], the coproduction of all the three genes (TEM + SHV + CTX-M) was 10.52% prevalent in the samples they studied in Burkina Faso, and this low figure seems to tally with the 10% and 5% prevalence seen in this work in K. pneumonia and E. coli respectively. Similar result was also reported by [18] in which all the three genes carried 9.09% prevalence.…”
Section: Discussionsupporting
confidence: 53%